Short-Term Waterlogging in Citrus Rootstocks - Margarita Pérez-Jiménez; Olaya Pérez-Tornero (Plants, 2021)
Changes in climate are provoking flooding events that cause waterlogging in the fields. Citrus are mainly cultivated in areas with a high susceptibility to climate change. Therefore, it is vital to explore their responses to these events to anticipate future challenges by means of genetic improvement of the commercial rootstocks. In this experiment, three popular commercial rootstocks, namely ‘Cleopatra’ (C. reshni Hort. Ex Tanaka), C. macrophylla, and ‘Forner Alcaide no. 5′ (Citrus reshni Hort. Ex Tanaka × Poncirus trifoliata), were evaluated after being submitted to short-term waterlogging and a period of recovery of 7 days in each case. Photosynthesis rate and stomatal conductance decreased in ‘Cleopatra’, while in the other two genotypes they were maintained (C. macrophylla) or restored after recovery (‘Forner Alcaide no. 5′’). Relative water content and chlorophylls also decreased in ‘Cleopatra’. This indicates a deeper effect of flooding in ‘Cleopatra’, which suffered changes during flooding that were also sustained during the recovery phase. This did not occur in the other two rootstocks, since they showed signs of recovery for those parameters that decreased during waterlogging.